2013
DOI: 10.1021/jp407447p
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Surface Plasmon on Cu(111) as an Excitation in the Mid-Infrared Range

Abstract: We report on an investigation of the acoustic surface plasmon on Cu(111), an electronic excitation in the infrared range related to the Shockley surface state. As shown here by high-resolution electron energy loss spectroscopy, it contributes together with other low-energetic electronic transitions to a broad excitation feature. Our analysis is similar to that recently reported for the Au(111) surface and clarifies that the group velocity of the acoustic surface plasmon is slower than the Fermi velocity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…31), in the considered 2D electron system the collective-excitation mode has a linear dispersion o pl q ð Þ $ q due to screening by the underlying three-dimensional electron system 25 . This mode is the aforementioned ASP, which was predicted to exist at metal surfaces with a partly occupied surface-state band 25,26 and was recently observed on Be 32 , Cu 33,34 and Au 35,36 surfaces by electron-energy-loss spectroscopy.…”
Section: Bulksupporting
confidence: 55%
“…31), in the considered 2D electron system the collective-excitation mode has a linear dispersion o pl q ð Þ $ q due to screening by the underlying three-dimensional electron system 25 . This mode is the aforementioned ASP, which was predicted to exist at metal surfaces with a partly occupied surface-state band 25,26 and was recently observed on Be 32 , Cu 33,34 and Au 35,36 surfaces by electron-energy-loss spectroscopy.…”
Section: Bulksupporting
confidence: 55%
“…Shockley surface states existing at the (1 1 1) surfaces of noble metals [56,149,[366][367][368][369][370][371][372][373][374] support this collective excitation, which owes its existence to the spatial coexistence of a 2DEG with a 3D electron gas. In Ag the excitation is ascribed to the screening of the Shockley surface states electrons by bulk electrons [367,375], while recent results have indicated that in both Au [150] and Cu [376] the opposite phenomenon occurs: slow bulk electrons are screened by the faster surface state electrons. Both types of interplay lead to an acoustic (sound-like) dispersion relation, giving the excitation its name ASP.…”
Section: Predictions Of Asp In (1 1 1)-oriented Ag Filmsmentioning
confidence: 99%
“…Later on Electron Energy Loss Spectroscopy experiments have confirmed the presence of the ASP mode at the Be(0001) [5,6] and noble metal surfaces [7][8][9][10][11][12][13][14] in good agreement with calculations and graphene adsorbed on metal substrates [15][16][17][18][19][20][21][22]. In cases when surface localized quantum well states are formed, e.g.…”
Section: Introductionmentioning
confidence: 54%